Controversies in the Management of Endometrial Carcinoma: An Update - Mohamed K. Mehasseb; John A. Latimer (Obstetrics and Gynecology International)
Endometrial carcinoma is the commonest type of female genital tract malignancy in the developed countries. Endometrial carcinoma is usually confined to the uterus at the time of diagnosis and as such usually carries an excellent prognosis with high curability. Our understanding and management of endometrial cancer have continuously developed. Current controversies focus on screening and early detection, the extent of nodal surgery, and the changing roles of radiation therapy and chemotherapy and will be discussed in this paper.